Drug Repurposing Based on Protozoan Proteome: In Vitro Evaluation of In Silico Screened Compounds against Toxoplasma gondii - Débora Chaves Cajazeiro; Paula Pereira Marques Toledo; Natália Ferreira de Sousa; Marcus Tullius Scotti; Juliana Quero Reimão (MDPI AG, 2022)
Toxoplasma gondii is a protozoan that infects up to a third of the world's population. This parasite can cause serious problems, especially if a woman is infected during pregnancy, when toxoplasmosis can cause miscarriage, or serious complications to the baby, or in an immunocompromised person, when the infection can possibly affect the patient's eyes or brain. To identify potential drug candidates that could counter toxoplasmosis, we selected 13 compounds which were pre-screened in silico based on the proteome of T. gondii to be evaluated in vitro against the parasite in a cell-based assay. Among the selected compounds, three demonstrated in vitro anti-T. gondii activity in the nanomolar range (almitrine, bortezomib, and fludarabine), and ten compounds demonstrated anti-T. gondii activity in the micromolar range (digitoxin, digoxin, doxorubicin, fusidic acid, levofloxacin, lomefloxacin, mycophenolic acid, ribavirin, trimethoprim, and valproic acid). Almitrine demonstrated a Selectivity Index (provided by the ratio between the Half Cytotoxic Concentration against human foreskin fibroblasts and the Half Effective Concentration against T. gondii tachyzoites) that was higher than 47, whilst being considered a lead compound against T. gondii. Almitrine showed interactions with the Na+/K+ ATPase transporter for Homo sapiens and Mus musculus, indicating a possible mechanism of action of this compound.